Effect of graphene nanofillers on the enhanced thermoelectric properties of Bi2Te3 nanosheets: elucidating the role of interface in de-coupling the electrical and thermal characteristics. (12th February 2018) - Kumar, Sunil; Singh, Simrjit; Dhawan, Punit Kumar; Yadav, R R; Khare, Neeraj
Abstract: In this report, we investigate the effect of graphene nanofillers on the thermoelectric properties of Bi2 Te3 nanosheets and demonstrate the role of interface for enhancing the overall figure of merit (ZT) ∼ 53%. The enhancement in the ZT is obtained due to an increase in the electrical conductivity (∼111%) and decrease in the thermal conductivity (∼12%) resulting from increased conducting channels and phonon scattering, respectively at the interfaces between graphene and Bi2 Te3 nanosheets. A detailed analysis of the thermal conductivity reveals ∼4 times decrease in the lattice thermal conductivity in contrast to ∼2 times increase in the electronic thermal conductivity after the addition of graphene. Kelvin probe measurements have also been carried which reveals presence of low potential barrier at the interface between graphene and Bi2 Te3 nanosheets which assist the flow of charge carriers thereby, increasing the mobility of the carriers. Thus, our results reveals a significant decrease in the lattice thermal conductivity (due to the formation of interfaces) and increase in the electron mobility (due to conducting paths at the interfaces) strongly participate in deciding observed enhancement in the thermoelectric figure of merit.